Differentiating feline inflammatory bowel disease from alimentary lymphoma in duodenal endoscopic biopsies. (1st June 2016) - Sabattini, S.; Bottero, E.; Turba, M. E.; Vicchi, F.; Bo, S.; Bettini, G.
Abstract : OBJECTIVES: This study aimed to evaluate the agreement between microscopic and molecular testing for differentiating feline intestinal bowel disease and small cell alimentary lymphoma in duodenal endoscopic biopsies. METHODS: Four different diagnostic methods (cytology, histology, immunohistochemistry and clonality) were sequentially applied to 77 cases of feline chronic enteropathies. The agreement between the different diagnostic methods was calculated and survival data were obtained to assess the most reliable method for predicting outcome. RESULTS: Seventy‐seven cases were included in the study. On multivariate survival analysis, only the clonality‐based diagnosis of lymphoma was significantly associated with poor survival, with a risk of enteropathy‐related death 2·8 times higher. By comparing the other tests with clonality, specificity was high (87 to 97%), whereas sensitivity was 36·8% for cytology, 39·5% for histology, 63·2% for immunohistochemistry, resulting in an overall accuracy of 62·3, 68·8 and 80·5%, respectively. CLINICAL SIGNIFICANCE: Clonality analysis can consistently increase the possibility of correctly and early diagnosing small cell lymphoma on endoscopic biopsies. Histological suspicion of alimentary lymphoma, even if not confirmed by clonality, should never be ignored, as it may represent a debutant form of lymphoma or it may later progress to lymphoma.